Effects of Eucalyptus Essential Oil on Growth, Immunological Indicators, Disease Resistance, Intestinal Morphology and Gut Microbiota in Trachinotus ovatus - Ziyang Lin; Shengzhe An; Chuanpeng Zhou; Yaqi Chen; Zhenchuang Gao; Juan Feng; Heizhao Lin; Pengwei Xun; Wei Yu (Microorganisms)
Essential oils serve as potential additives that can enhance immune respons and disease resistance and regulate the gut microbiota of fish. Here, this research aims to identify the impacts of eucalyptus essential oil (EEO) on growth, liver antioxidative and immune parameters, resistance to Streptococcus iniae, intestinal morphology and gut microbiota in Trachinotus ovatus. All fish (initial weight: 26.87 ± 0.30 g) were randomly allocated to 12 floating cages (2.0 × 2.0 × 2.0 m3) with each cage containing 100 fish and fed for 30 days. Four diets were manufactured with the supplementation of varying levels of EEO (control and 5.0, 10.0, and 15.0 mL/kg) and were named CG, EEO1, EEO2 and EEO3, respectively. The results showed that EEO1 and EEO2 diets significantly increased WGR, thickness of the intestinal muscle layer, and the ratio of villus height to crypt depth (V/C), while decreasing the intestinal crypt depth of T. ovatus (p < 0.05). Significantly increased activities of SOD and CAT and significantly reduced MDA levels were present in the EEO1 and/or EEO2 groups (p < 0.05). Moreover, the mRNA levels of nrf2, HO-1, GSH-Px, SOD, C4 and GR genes were significantly upregulated and the expression of keap1 and HSP70 genes were significantly downregulated within the EEO1 and EEO2 groups (p < 0.05). After challenge with S. iniae B240703 for 24 h, the bacterial load for five organs in the EEO2 group was less than that in the CG group (p < 0.05). In addition, the fish fed EEO1 and/or EEO2 diets had significantly lower abundances of pathogenic bacteria (Proteobacteria, Planctomycetota, Burkholderia-Caballeronia-Paraburkholderia, Pseudomonas and Blastopirellula) and a higher beneficial bacteria proportion (Firmicutes) than those fed the CG diets (p < 0.05). In conclusion, a moderate dietary m EO level (5.0~10.0 mL/kg) improved the growth and gut morphology, promoted liver immune response, enhanced resistance to S. iniae and modulated the gut microbiota of T. ovatus.